Mapping The Strategic Manoeuvring Through Speech Acts: A Study of Ferry Irwandi’s Political Argumentation in YouTube - Nauvalia hanidia; Syihabuddin; Mahardhika Zifana (Universitas Islam Negeri Palopo, 2026)
This study examines how Ferry Irwandi employs speech acts as strategic manoeuvring in his political argumentation on YouTube, specifically in the video “Dalang Demo dan Mencegah Darurat Militer.” While previous studies on political discourse have largely examined strategic manoeuvring or speech acts separately, limited attention has been given to how speech acts function as concrete linguistic mechanisms for balancing dialectical and rhetorical aims in digital political argumentation. To address this gap, this study applies a descriptive qualitative method within the pragma-dialectical framework to analyze the relationship between speech acts and strategic manoeuvring. The analysis covers seven argumentative units, each systematically divided into the four stages of argumentation: confrontation, opening, argumentation, and concluding. In each stage, the forms and functions of direct and indirect speech acts are identified to examine how they fulfill the three aspects of strategic manoeuvring: topical potential, audience demand, and presentational devices. The results of the analysis show that direct-representative speech acts are the most dominant with 17 data and function to clarify claims and strengthen the argument structure. Meanwhile, indirect speech acts with 10 data are used to meet the audience's demand through a more empathetic approach, and directive speech acts with 5 data appear at the conclusion to encourage action. These three linguistic patterns work simultaneously in a strategic manoeuvring, where representatives strengthen topical potential, directives strengthen presentational devices, and indirect speech acts build audience demand.